2018
DOI: 10.4028/www.scientific.net/msf.927.112
|View full text |Cite
|
Sign up to set email alerts
|

Effect of TIG-Welding on the Structure and Mechanical Properties of the Pseudo-β Titanium Alloy VT19 Welded Joints

Abstract: Analysis of the TIG-welding impact on the structure and mechanical properties of pseudo-β titanium alloy VT19 welded joints, obtained with different welding speed, different filler wire amount in welded joint, with and without flux layer. Microstructure of obtained welded joints were investigated. Using welded joints microsections approximate amount of β-phase in different parts of welds have been obtained. Mechanical properties of the obtained welded joints were analyzed and dependency of tensile strength and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 18 publications
0
1
0
Order By: Relevance
“…For this research, two types of TIG-welding were used: standard fusion TIG welding and TIG welding on the thin flux layer. For standard fusion TIG welding, the tungsten electrode is not located below the surface of the weld metal, with the pre-set arc length approximately 0.5...1 mm [22]. Welding modes are selected to achieve complete fusion of the base metal as the arc progresses.…”
Section: Research Methods and Materialsmentioning
confidence: 99%
“…For this research, two types of TIG-welding were used: standard fusion TIG welding and TIG welding on the thin flux layer. For standard fusion TIG welding, the tungsten electrode is not located below the surface of the weld metal, with the pre-set arc length approximately 0.5...1 mm [22]. Welding modes are selected to achieve complete fusion of the base metal as the arc progresses.…”
Section: Research Methods and Materialsmentioning
confidence: 99%
“…Additionally, the microstructure of the fusion zone (FZ) was composed of coarse β grains and acicular α and α' phases. Akhonin et al [15] investigated the influence of TIG welding on the microstructure and mechanical properties of a VT19 titanium alloy welded joint. Hu et al [16] demonstrated that the HAZ and FZ of the TC17 titanium alloy TIG welded joint are composed primarily of α' martensite, acicular α, and Widmanstätten α + β, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…It is used to create products for construction purposes, railway cars, frame structures in rocket building, etc. As compared to continuous welding [24][25][26][27][28][29][30][31][32], spot welding [6,10,19] provides minimal deformations of structures and allows manufacture them with a high accuracy. The use of spot welding provides high efficiency and quality of performed works and saves time and material resources due to reduction of efforts to straighten products, required because of their buckling after welding and decrease in electric power consumption.…”
Section: Introductionmentioning
confidence: 99%